The Effect of Capital Restructuring on Bank Financial Performance - Okonkwo, Jisike Jude; Okere, Wisdom; Okoye, Nonso John; Mkparu, Ekene Trinity (AKRUAL: JURNAL AKUNTANSI, 2023)
Introduction/Main Objectives: The purpose of this research was to analyze how capital restructuring affected the profitability of Nigerian banks. The study's stated goals were to determine whether or whether the Return on Assets of Deposit Money Banks in Nigeria was affected by the Debt-Equity Ratio, the Capital Adequacy Ratio, and the Change in Equity. Financial economics theory served as the basis for this investigation. Background Problems: Capital restructuring has progressed over time in response to dynamic economic conditions, globalization, market competition, and technological advancements. Novelty: This study was conducted on banks in Nigeria using panel data regression.. Research Methods: This research use the panel least square regression test to examine the relationship between the debt-equity ratio, the capital adequacy ratio, and the change in equity, and the Return on Asset of money deposit institutions. The direction of causality between the dependent and independent variables was determined using the Granger Causality test. Finding/Results: Debt-to-equity and capital-adequacy ratios were found to have a negative and insignificant relationship with DMBs' return on assets in Nigeria, while changes in equity were found to have a positive and statistically significant relationship with DMBs' return on assets during the study period. Conclusion: Therefore, it suggests that additional equity funding be made available. A bank's financial performance may be improved by using debt solely as a last option.